A high content (30%) stable doxycycline hyclate drinking-water solution for broilers: preparation, stability, and bioequivalence - Liu, Ziyao; Jiao, Xiaojun; Xie, Linhua; Ren, Wenge; Lv, Linyi; Du, Juan; Huang, Xianhui (Frontiers in Veterinary Science, 2026)
IntroductionDoxycycline is a semi-synthetic tetracycline antibiotic with broad-spectrum antimicrobial activity. Under intensive animal husbandry, commercially available doxycycline drinking-water formulations often show several drawbacks in solubility, stability and homogeneous distribution under farm conditions. To overcome these limitations, we developed a high content (30%, w/v), pilot-scale, stable doxycycline hyclate solution (DOX·HCl solution) specifically designed for drinking-water administration. A comprehensive quality assessment of this system was performed, followed by a bioequivalence evaluation of its application in broilers.MethodPrescription selection through high-temperature testing was combined with preparation process study via single-factor screening to prepare DOX·HCl solution. Quality assessment included assay of DOX, the dilutability and dilution stability testing, evaluation of mixed performance, and the stability studies. Bioequivalence study was conducted in a randomized, parallel, and blinded design to compare the DOX·HCl solution with two commercially available doxycycline hyclate drinking-water products.ResultsThree pilot-scale batches of the 30% DOX·HCl solution (mean content 100.14 ± 0.37%) were successfully manufactured under controlled conditions of 400 rpm stirring and 60 °C. These pilot samples remained stable in appearance and content when diluted with water for up to 24 h. Affecting factor testing, accelerated testing and long-term testing all showed good stability, with an expiration date exceeding 24 months. In broilers, the DOX·HCl solution achieved a Tmax of 3.19 ± 0.86 h, t1/2 of 6.47 ± 2.77 h, Cmax of 7.69 ± 2.27 μg/mL, and AUC0-t of 79.48 ± 23.88 h·μg/mL. There was no significant difference (p > 0.05) in the main pharmacokinetic parameters among the experimental broiler groups, and 90% CI values were within 80–125%, indicating that the 30% DOX·HCl solution was bioequivalent to the commercially available drinking-water formulations.ConclusionThe 30% DOX·HCl solution represents a high-content, industrially scalable drinking-water concentrate that combines long-term physicochemical stability with bioequivalence to existing products. This formulation offers a more convenient and highly efficient reliable option that could be a potential alternative to commercial products for mixed drinking-water medication of livestock and poultry, particularly under high-density, centralized management conditions.